INVESTIGACIÓN CUANTITATIVA E INVESTIGACIÓN CUALITATIVA: BUSCANDO LAS VENTAJAS DE LAS DIFERENTES METODOLOGÍAS DE INVESTIGACIÓN - Ugalde Binda, Nadia (2022)
the research process has as a result the creation of knowledge through solving a researchproblem. thus, research methodology refers to all the decisions that the researcher makesto achieve their research goals and deals with issues such as research design, the strategyto use, the study sample, the methods used to collect the information, techniques to beused in the analysis of information and the criteria to be used to increase the quality ofwork, among others. the current research designs revolve around two major paradigms:quantitative model and the qualitative model. this article reviews both perspectives andexplains when and why it is appropriate to use each one.